Project-Based Learning Concept Map in Vocational Education - Aliyah Rasyid Baswedan; Fitri Nur Mahmudah (Linguanusa : Social Humanities, Education and Linguistic, 2023)
Introduction to The Problem: Along with the times, the learning process in schools, especially in vocational education, needs to be improved. Likewise, teacher competencies and skills are expected by the industry, so the learning process emphasizes improving work competencies. Purpose: This study aims to explore learning in project-based vocational education to produce a concept map that can be used for competency development for vocational teachers. Design/methods/approach: This research is a literature review with a systematic literature review approach. The data used are the results of publications that are relevant to the research theme. The results of the publications used were found in various journal databases. Findings: The PjBL approach is used as a learning method that can help the process of critical and creative thinking, raising problem issues in the community.  Students play a role in solving problems in their scientific fields. Based on the findings of the research results/concept map produced, this study has a novelty consisting of five components in the PjBL learning model in SMK, namely the learning model component, learning step, skills, supporting factors, and competency achievement. Research implications/limitations: The results of this study have a direct impact on vocational education units, especially school principals and productive teachers to be able to develop learning competencies through the right approach in accordance with student needs and the relevance of competencies expected by the industry. In the end, the learning process carried out can be used as capital and basis for students and graduates for employment and absorption of graduates. Originality/value: This research is a literature study so it needs to be redeveloped through various research approaches so that the expected results can be implemented in vocational education units.